Study on the Multi-Governance of Public Rental Housing Exit in China Based on the Evolutionary Game Theory. (23rd May 2022) - Tang, Jing; Li, Shilong
Abstract : The COVID-19 pandemic has plunged the housing affordability and living sanitary conditions of China's low-income groups into a crisis. Public rental housing has made a significant contribution to alleviating this crisis, yet its exit problem has become more acute due to the impact of the epidemic. In order to explore how to effectively play the role of multi-governance in public rental housing exit, this paper adopts game theory to analyze the evolution of the behavioral strategies of government departments and public rental housing tenants in public rental housing exit by combining four influencing parameters: the epidemic severity, the epidemic influence coefficient, the public participation degree, and the public reporting fairness. In response to exploring the conditions for the effective functioning of the multi-governance model under the impact of the epidemic, the influences of parameter change on the stability of the system are analyzed. The results show that when the COVID-19 epidemic impact coefficient is high, government departments need to reduce their own supervision costs to achieve better multi-governance effects; when public reports are distorted, the government departments' own supervision capabilities determine the impact of public participation on governance effects.